Azimuthal Adaptation of the Moon-Based Raṣdu al-Qiblah Method - Azmi, Muhammad Farid; Yaqin, 'Alamul (Al-Hilal: Journal of Islamic Astronomy, 2025)
The Raṣdu al-Qiblah of the Moon is a night-time method for determining Qibla direction, but it can only be used once per night and not on specific dates due to natural limitations. This study introduces an innovation by applying azimuth difference values (+90°, +45°, -45°), allowing the method to be used multiple times a night. The research compares this enhanced method with theodolite measurements and the Raṣdu al-Qiblah of the Sun to test its accuracy. Using a qualitative approach with astronomical analysis, the study finds that this modified method results in a deviation between 0°9'32.96" and 0°57'17.43". These results fall within acceptable Qibla tolerance limits as defined by some experts, showing that this method is accurate and viable as an alternative for Qibla determination, especially at night.